Around Decade : Polish Photography of 90s. - Borusiewicz, Miroslaw; Hermansdorfer, Mariusz; Jurecki, Krzysztof; Sobota, Adam; Wicherkiewicz, Magdalena (Lódz : Muzeum Sztuki Lodz, 2002)
Andrzejewska, Ewa ; Barszczak, Wieslaw ; Bartolowicz, Jaroslaw ; Bohdziewicz, Anna Beata ; Cichosz, Krzysztof ; Dlubak, Zbigniew ; Gardulski, Marek ; Golec, Leszek ; Czekalska, Tatiana ; Jama, Waldemar ; Kizny, Tomasz ; Komorowski, Tomasz ; Konopka, Bogdan ; Kubala, Slawomir ; Kulik, Zofia ; Kuzyszyn, Konrad ; Lachowicz, Andrzej ; Lech, Andrzej J. ; Lesniak, Jan ; Lazikowski, Edward ; Kaliska, Lodz ; Mikolajczyk, Antoni ; Natalia LL ; Nawrot, Irena ; Orzechowska, Patrycja ; Pozniak, Marek ; Prazmowski, Wojciech ; Pruszkowski, Krzysztof ; Przyborek, Grzegorz ; Robakowski, Jozef ; Rydet, Zofia ; Rytka, Zygmunt ; Skapski, Lukasz ; Szurkowski, Leszek ; Tomaszczuk, Zbigniew ; Truszkowski, Jerzy ; Wesolowski, Leszek ; Wegrzyn, Witold ; Wojnecki, Stefan ; Wolynski, Piotr ; Wos, Stanislaw J. ; Lyyying Community ; Zastrózna, Joanna ; Zawadzki, Wojciech ; Zak, Pawel
Diary of more Important Photographic and Interdysciplinary Exhibitions in Poland and Abroad between 1989-2001 (selection) p. 33-37
biog. per kunstenaar
ind. tent., collecties, bibliog. p. 128-142
Pools & Engels
Around decade : Polish Photography of 90s, Muzeum Sztuki, Lodz, 08.03.2002 - 07.04.2002
boek
Keywords: Polen